Radio and television in “Aprendo en casa”: findings by open coding - Alarcón-Llontop, Luis-Rolando (2021)
This research is about what the “Aprendo en casa” strategy in Peru in 2020 meant from two of its main resources, radio and television. The objective was to analyze communicationally and evaluate the programs of both media. Thirty-two pieces from all educational levels were discussed, in seven months, with 27 expert communicators, and the experience from 50 target actors of the strategy was evaluated. The study was methodologically naturalistic, with a qualitative approach, indirect hermeneutical and phenomenological typologies, and under an open coding design. Eight categories generated by free will were found to show results on biased content and questionable forms of presentation; gaps were made visible at the educational, digital, and generational levels, and disarticulation between the education and communication axes. Our findings will contribute to improve the design and use of media resources in favor of the educational foray analyzed and the like.